VARIASI PEMBELAJARAN MATEMATIKA DI Ã¢â¬ÅSEKOLAH Ã¢â¬â RUMAHÃ¢â¬Â BAGI PARA HOMESCHOOLER - Abidin, Zaenal (Lembaran Ilmu Kependidikan, 2007)
Homeschooling is a relatively new term in the Indonesian education. TheDepartment of National Education (Depdiknas) officially introduces homeschooling as"Sekolah-Rumah". Homeschooling emerges from persistent problems the nationaleducation system faces, such as the frequent changes of curriculum, pros and cons ofthe national examination and examination passing criteria, student enrollment system,and the very expensive education cost. Based on those grounds, homeschoolingbecomes an education alternative for parents to develop their childrenÃ¢â¬â¢s potency. Inhomeschooling, there is no limitation in developing the model of mathematicsteaching. The teaching method applied is one that suits the childrenÃ¢â¬â¢s learning stylebest. To improve the effectiveness of mathematics teaching in homeschooling, thingsand activities of the childrenÃ¢â¬â¢s daily life are used. The challenge of the parents inteaching mathematics to homeschool students is how to understand mathematicconcepts which are relevant to the chosen homeschoool curriculum and how totransform them into ideas adjusted to childrenÃ¢â¬â¢s competence.Kata kunci: Homeschooling, sekolah-rumah, pembelajaran matematika